The distribution of North Atlantic right whales in Canadian waters from 2015-2017 revealed by passive acoustic monitoring - Durette-Morin, Delphine; Evers, Clair; Johnson, Hansen D.; Kowarski, Katie; Delarue, Julien; Moors-Murphy, Hilary; Maxner, Emily; Lawson, Jack W.; Davies, Kimberley T. A. (Frontiers in Marine Science, 2022)
Northward range shifts are increasingly being identified in mobile animals that are responding to climate change. Range shifts are consequential to animal ecology, ecosystem function, and conservation goals, yet for many species these cannot be characterised without means of synoptically measuring their distribution. The distribution of critically endangered North Atlantic right whales (Eubalaena glacialis; NARW) north of 45oN has been largely unknown due to a lack of systematic monitoring. The objectives of this study were to characterize the spatial and temporal variation in NARW acoustic occurrence in the northern portion of their foraging range. In addition, we sought to identify relevant NARW migratory corridors and explore potential previously unidentified high-use habitats beyond the highly surveyed Gulf of St. Lawrence (GSL). To achieve this, passive acoustic monitoring data were collected and analyzed from 67 moorings and 13 gliders deployed (across 38 recording stations) throughout the Atlantic Canadian continental shelf, between 42oN and 58oN during 2015 through 2017. The results support that while a portion of the population has moved northward into the GSL, this shift was constrained to temperate latitudinal ranges < 52oN during the study period. NARWs were not detected in the Labrador Sea and Newfoundland Shelf, despite their preferred prey occurring in those areas. NARWs were present on the Scotian Shelf (45oN) nearly year-round, but only from May through December in the Cabot Strait (50oN). These results suggest that the northern range of the population is probably influenced by energetic requirements to minimize the distance between suitable foraging habitat and low latitude calving grounds, rather than an absence of suitable foraging conditions in high latitude waters, or other environmental or physiological factors. This work provides critical information to conserve the species and mitigate human-induced risks.